Difusi Norma Melalui Media: Al Jazeera dan Respons Masyarakat Sipil Global Indonesia atas Konflik Israel–Palestina (2023–2024) - Prima, Joy; Setyaka, Virtuous; Jamilah, Maryam (Palito, 2025)
The Israeli-Palestinian conflict continues to be a global issue that receives widespread attention, including in Indonesia. As an international media outlet, Al Jazeera plays a significant role in framing the narrative of this conflict through its reporting. This study aims to describe Al Jazeera's role in influencing the Global Civil Society groups in Indonesia through its coverage of the Israeli-Palestinian conflict, using the Norm Life Cycle theory by Finnemore & Sikkink. This study uses a qualitative approach with a descriptive analytical approach. Primary data were obtained through in-depth interviews with representatives of three Global Civil Society groups in Indonesia: the Free Palestine Network (FPN), the National Committee for the Palestinian People of West Sumatra (KNRP Sumbar), and the Andalas University Student Justice for Palestine (UNAND SJP). Secondary data were collected through a literature review and framing analysis of nine Al Jazeera news articles published between October 2023 and October 2024. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings indicate that Al Jazeera plays a norm entrepreneur role in shaping and disseminating norms. Al Jazeera has successfully shaped, disseminated, and internalized key norms through its reporting. The norms of resistance to colonialism, protection of non-combatants, and upholding human rights have been adopted by MSG groups in Indonesia. This research is limited to the 2023–2024 period and involves only three of the four planned Global Civil Society groups. The analysis also focuses on the global level without involving state actors.